Switching identities: a revision of the Afrotropical spider genus Carteronius Simon, 1897 (Araneae, Corinnidae), senior synonym of Mandaneta Strand, 1932, with a new genus of the Pronophaea group - Bonaldo, Alexandre B.; Bosselaers, Jan; Ramírez, Martín J.; Labarque, Facundo M.; Shimano, Yulie; Silva-Junior, Cláudio J.; Haddad, Charles R. (Zootaxa, 2022)
The genus Carteronius Simon, 1897 is transferred from Clubionidae to Corinnidae and recognized as the senior synonym of Mandaneta Strand, 1932, being the oldest available name for the pre-occupied Mandane Karsch, 1880. Upon comparing the respective type specimens, the type species of Carteronius and the type species of Mandaneta were found to represent the same species. Whence the type species Carteronius helluo Simon, 1896, is considered a junior synonym of the type species Mandaneta sudana (Karsch, 1880). Three other species of Carteronius are transferred to Donuea Strand, 1932 (Corinnidae): D. fuscus (Simon, 1896) comb. nov. from Mauritius, D. vittiger (Simon, 1896) comb. nov. and D. argenticomus (Keyserling, 1877) comb. nov., both from Madagascar. The type species, Carteronius sudanus comb. nov., from Côte d’Ivoire, Democratic Republic of the Congo, Ghana, Guinea, Sierra Leone, and C. gentilis (Simon, 1909) comb. nov., from Equatorial Guinea and Cameroon (the latter transferred from Procopius Thorell, 1899) are redescribed, and the female of C. gentilis is described for the first time. Six new species of Carteronius are described: C. ashanti Bonaldo & Silva-Junior sp. nov. from Ghana, C. myene Bonaldo & Labarque sp. nov., and C. simoni Bonaldo & Shimano sp. nov. from Gabon, C. lumumba Bonaldo & Ramírez sp. nov. from Cameroon, Gabon and the Democratic Republic of the Congo, and C. arboreus Bonaldo & Haddad sp. nov. and C. teke Bonaldo & Bosselaers sp. nov. from the Democratic Republic of the Congo. A key and distribution maps to all eight species in the genus are presented. The related Bunyoronius Bonaldo, Ramírez & Haddad gen. nov. is proposed to include B. femoralis Bonaldo, Ramírez & Haddad sp. nov. from the Central African Republic, Uganda, and Rwanda.